Nutrition outcomes in women and children in rural farming households - Geremew, Kumlachew; Madzivhandila, T.; Sibanda, S.; Majele, L.; Mkhandawire, B.; Gunaratna, N.; Kinabo, J.; Dessie, Tadelle (2019)
A cluster-randomized study design has evaluated the effect of the ATONU and ACGG interventions on the primary outcome of dietary diversity among women of reproductive age in smallholder poultry producing households. Data were collected between November 2016 and May 2018 at three time points: baseline prior to the start, midline, and end line after completion of ATONU interventions. A total of 2,117 households were enrolled in the study. Among these, 710 belonged to the ACGG, 709 to the ACGG+ATONU, and 698 to the control arm. The village level questionnaire was administered in each village at baseline and endline. The outcomes showed that the consumption of chicken meat and egg in the ACGG+ATONU increased by 5% as compared to ACGG and by 23% as compared to the Control group. Women’s participation was highest (more than 90%) at all three time points for chicken related production activities and use of eggs for home consumption. The knowledge of exclusive breastfeeding and complementary feeding practices for young children was high across time and treatment arms. The food consumption diversity improved from baseline (18.3%) to midline (24.5%), and end line (28.3%). 55.7% of children were anemic at baseline compared to 32.4% at end line. We see moderate improvements in dietary diversity over time in all three arms, with relatively greater increases among the ACGG+ATONU arm. This suggests that poultry interventions alone may not influence dietary diversity and should therefore be coupled with BCC for greatest impact.